The 20th Asia and South Pacific Design Automation Conference 2015
DOI: 10.1109/aspdac.2015.7059029
|View full text |Cite
|
Sign up to set email alerts
|

A retargetable and accurate methodology for logic-IP-internal electromigration assessment

Abstract: Abstract-A new methodology for SoC-level logic-IP-internal EM verification is presented, which provides an on-the-fly retargeting capability for reliability constraints. This flexibility is available at the design verification stage, in the form of allowing arbitrary specifications (of lifetimes, temperatures, voltages and failure rates), as well as interoperability of IPs across foundries. The methodology is characterization-and reuse-based, and naturally incorporates complex effects such as clock gating and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Chen et al [13] considered varying temperature and current requirements at run time for the EM effect analysis. Jain et al emphasized the importance of considering EM reliability across the whole workflow from foundry fabrication up to a system design [38]. Guan and Marek-Sadowska [39] analyzed the EM effect on signal line reliability, which carries ac current, and proposed a theoretical model to quantify healing effect due to ac currents.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [13] considered varying temperature and current requirements at run time for the EM effect analysis. Jain et al emphasized the importance of considering EM reliability across the whole workflow from foundry fabrication up to a system design [38]. Guan and Marek-Sadowska [39] analyzed the EM effect on signal line reliability, which carries ac current, and proposed a theoretical model to quantify healing effect due to ac currents.…”
Section: Related Workmentioning
confidence: 99%
“…Li et al [2] concentrated on EM effect on power grid interconnect vias and explored the tradeoff between power signal integrity and area overhead. Jain et al [38] proposed a new methodology to evaluate the EM effect on system-on-chips by separately characterizing individual current components and try to make retargeting reliability specifications across different markets or block levels within a chip. Chen et al [13] considered varying temperature and current requirements at run time for the EM effect analysis.…”
Section: Related Workmentioning
confidence: 99%
“…In the most previous studies of EM modeling, the Black's equation and Blech limit are applied to analyze the reliability of signal interconnects and power grids [66][67][68][69][70][71][72][73]. In [66][67][68], by incorporating the Joule heating effect, Gracieli Posser et al have developed approaches for modeling and efficient characterization of cell-internal EM and have simulated EM effects on different metal layers at different wire lengths.…”
Section: Modeling Of Em Impact On Power Gridsmentioning
confidence: 99%
“…On the other hand, it is concluded that larger metal layers have smaller EM effects and, consequently, a higher EM lifetime for the wires. Palkesh Jain et al proposed a SoC-level logic-IP-internal EM verification methodology which provides onthe-fly retargeting capability for reliability constraints [69,70]. The proposed approach is demonstrated on a 28-nm design.…”
Section: Modeling Of Em Impact On Power Gridsmentioning
confidence: 99%
“…Table 5. 1 As discussed earlier in Section 5.4, the current density in a given resistor is a weighted summation of the individual gate currents ((5.16)), wherein the position of the resistor in the power grid affects the weightages. Unlike global variations, which are fully correlated, the local variations are independent and uncorrelated.…”
Section: Evaluation Of the Hermite Pc Approachmentioning
confidence: 99%